Determination of Dietary Exposure to β-Carboline Alkaloids for Food Safety Management - Cho, Yoeseph; Hwang, Sungmin; Park, Saeyeon; Heo, Soohyun; Moon Jihwan; Park, Hana; Lee Hyun Jeong; SON, Jung hyun (제73회 한국분석과학회 추계학술대회 [초록집], 2024)
β-Carboline (βC) alkaloids, which belong to the class of indole alkaloids inherent in plant materials, can naturally occur in food ingredients but can also be generated during food processing. βC alkaloids possess pharmacological effects; however, there have been reports of human health risks depending on the level of consumption. As dietary trends change, the potential exposure to these latent toxins has increased, highlighting the need to establish a safety management system. Therefore, this study was conducted to monitor the levels of βC alkaloids in foods and to determine the dietary exposure to βC alkaloids. A total of 1,365 samples from 113 food items distributed in South Korea were selected for monitoring. The collected samples were rapidly and simultaneously analyzed for six βC alkaloids using a QuEChERS-based high-sensitivity liquid chromatography-tandem mass spectrometry method developed in this study. The analysis results showed that the primary detected βC alkaloids were norharman and harman, which were found in 56.3% and 48.7% of the total samples, respectively. Many of the top-detected items included those that underwent processing, and significant increases were observed in heat-processed products within the same category. Based on the monitoring results, we calculated the estimated daily intake of six types of βC alkaloids exposed through dietary consumption, which accounted for 51.0% of the total daily dietary intake of the Korean population. The dietary exposure to βC alkaloids derived from this study was considered insufficient to induce toxicity in the body compared to previous toxicity studies. In this study, we determined the levels of βC alkaloids in various foods and calculated dietary exposure to understand the risks associated with βC alkaloids related to food consumption. Our research findings will serve as essential foundational data for ensuring food safety.